Characterization of counterfeit artesunate antimalarial tablets from southeast Asia. - Hall, K; Newton, P; Green, MD; De Veij, M; Vandenabeele, P; Pizzanelli, D; Mayxay, M; Dondorp, A; Fernandez, F (2006)
In southeast Asia, the widespread high prevalence of counterfeits tablets of the vital antimalarial artesunate is of great public health concern. To assess the seriousness of this problem, we quantified the amount of active ingredient present in artesunate tablets by liquid chromatography coupled to mass spectrometry. This method, in conjunction with analysis of the packaging, classified tablets as genuine, substandard, or fake and validated results of the colorimetric Fast Red TR test. Eight (35%) of 23 fake artesunate samples contained the wrong active ingredients, which were identified as different erythromycins and paracetamol. Raman spectroscopy identified calcium carbonate as an excipient in 9 (39%) of 23 fake samples. Multivariate unsupervised pattern recognition results indicated two major clusters of artesunate counterfeits, those with counterfeit foil stickers and containing calcium carbonate, erythromycin, and paracetamol, and those with counterfeit holograms and containing starch but without evidence of erythromycin or paracetamol.